Evaluation of Stunting Countermeasures Strategies in Indonesia - Azhara, Ratu Raisya Aghnia; Deliarnoor, Nandang Alamsah; Sagita, Novie Indrawati (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
Stunting is a major health problem for toddlers in Indonesia. To prevent and overcome stunting in Indonesia, the central and regional governments have established various policies and programs to accelerate stunting reduction. This study aims to evaluate government policies and programs from existing studies on the government's strategy for tackling stunting cases in Indonesia. This study used a systematic review method on case study journals indexed by Sinta with the keyword "Stunting Prevention and Management" searched through the Google Scholar database with a range of 2019 - 2023. Based on the researcher's search, five journals met the following criteria. Evaluation based on input, process, and output parameters from case studies on preventing and controlling stunting in Indonesia. The results of a systematic review show that the process of preventing and overcoming stunting in Indonesia is quite good but not optimal. The Covid-19 pandemic is one of the factors causing the process of preventing and overcoming stunting in Indonesia not to be optimal. At the same time, other problems include limited human resources, financing, and inadequate facilities or facilities in several areas.